Risk Classification and Automobile Insurance Premiums – A study on the Perceptions of Cypriot Policyholders on the Fairness of Automobile Risk Classification Variables - Zachariadou, Antonia (2010)
The intention of this study is to investigate the opinions of Cypriot insured drivers regarding the fairness of particular risk classification variables. Classification variables include, amongst others, age, gender, years of driving experience and driver record. The aim of this research paper is also to establish whether significant associations exist between the opinions of Cypriot insured drivers and a number of demographic and other policyholder characteristics which are used to set premiums in automobile insurance.